Expression of the hybrid bacteriocin Ent35-MccV in Lactococcus lactis and its use for controlling Listeria monocytogenes and Escherichia coli in milk - Acuña, Leonardo (2020)
Bacteriocins are antimicrobial peptides synthesised ribosomally. One of the main drawbacks of bacteriocins as food biopreservative agents is their restricted action spectrum. To obtain a broad-spectrum bacteriocin-producing lactic acid bacterium, we engineered a fusion protein between the enterocin P signal peptide and the broad-spectrum chimerical bacteriocin Ent35-MccV. Lactococcus lactis NZ9000 transformed with the recombinant plasmid (pRUK) was tested to identify the bacteriocin production by antimicrobial activity and colony MALDI-TOF mass spectrometry. Additionally, we performed mixed cultures in skim milk to determine the inhibition of Lc. lactis NZ9000 (pRUK) on both Listeria monocytogenes and Escherichia coli strains isolated from food. The results showed that Lc. lactis NZ9000 (pRUK) was able to diminish the growth of both L. monocytogenes and E. coli in skim milk due to Ent35-MccV production. Ent35-MccV is the first linear, genetically engineered bacteriocin produced in situ in food products used effectively to control Gram-negative and Gram-positive foodborne pathogens.